(untitled) (Fiep Bulletin - online, 2014)
This article studies the historical relations that established between the body and power. In these relations we observe that in a given moment we lose ownership of our body and that it starts to become a favorite target of domination and loss of identity. These characteristics shun the human being from a conscience of its body that would be made possible through knowledge of its corporeity as way of being, where the man presents himself in the world through a body that moves itself in search to transcend in the meaning of being more. This search creates the perspective and necessity of the coming of the active body. Here we discuss the active body not in the sense of performance, effectiveness and aesthetics, but the active body for the conscience and necessity of the human motor skills which is proper of the body in act. We inquire and we reflect on the bodies that had been created in accordance with the interests that permeate the societies throughout history. We arrive at the requirements of the current standards, that invite all to a standardization, forgetting the subjectivity of the individual and creates a false corporal image, that largely contributes for it not to seek the discovery from inside-out and indeed that we remain in the superficiality.